Generalization and Induction: More Misconceptions and Clarifications - TSANG, Eric W. K. (Institutional Knowledge at Singapore Management University, 2012)
In ‘Generalization and Induction: Misconceptions, Clarifications, and a Classification of Induction’, we comment on Lee and Baskerville’s (2003) paper ‘Generalizing Generalizability in Information Systems Research’, which attempts to clarify the concept of generalization and classify it into four types. Our commentary discusses the misconceptions in their paper and proposes an alternative classification of induction. Their response ‘Conceptualizing Generalizability: New Contributions and a Reply’ perpetuates their misconceptions and create new ones. The purpose of this rejoinder is to highlight the major problems both in their original paper and in their reply and to provide further clarifications. Lee and Baskerville’s so-called ‘new language’ of describing research activities based on their concept of generalization is confusing. Their classification abuses the term ‘generalize’ and is self-contradictory. Hence, contrary to their claim, their classification and ours are not compatible. Also contrary to their claim that we advocate paradigmatic domination, our commentary is just about the correct use of terms such as ‘generalize’, ‘induction’ and ‘deduction’.